Foley catheter vs oral misoprostol for induction of labor: individual participant data meta‐analysis. (1st February 2021) - Kemper, J. I.; Li, W.; Goni, S.; Flanagan, M.; Weeks, A.; Alfirevic, Z.; Bracken, H.; Mundle, S.; Goonewardene, M.; ten Eikelder, M.; Bloemenkamp, K.; Rengerink, K. O.; et al.
ABSTRACT: Objective: To compare the effectiveness and safety of Foley catheter and oral misoprostol for induction of labor (IOL). Methods: The Cochrane Review on Mechanical Methods for Induction of Labour and Ovid MEDLINE, EMBASE via Ovid, Ovid Emcare, CINAHL Plus, ClinicalTrials.gov and Scopus, from inception to April 2019, were searched for randomized controlled trials (RCTs) comparing Foley catheter to oral misoprostol for IOL in viable singleton gestations. Eligible trials for which raw data were obtained were included and individual participant data meta‐analysis was performed. Primary outcomes were vaginal birth, a composite of adverse perinatal outcome (including stillbirth, neonatal death, neonatal seizures, admission to the neonatal intensive care unit, severe respiratory compromise or meconium aspiration syndrome) and a composite of adverse maternal outcome (including admission to the intensive care unit, maternal infection, severe postpartum hemorrhage, maternal death or uterine rupture). The quality of the included RCTs was assessed using the Cochrane Risk of Bias 2 tool and the certainty of evidence was evaluated using the GRADE approach. A two‐stage random‐effects model was used for meta‐analysis according to the intention‐to‐treat principle and interactions between treatment and baseline characteristics were assessed. Results: Of seven eligible trials, four provided individual participant data for a total of 2815 participants undergoing IOL, of whom 1399 were assigned to Foley catheter and 1416 to oral misoprostol. All four trials provided data for each of the primary outcomes in all 2815 women. Compared with those receiving oral misoprostol, Foley catheter recipients had a slightly decreased chance of vaginal birth (risk ratio (RR), 0.95 (95% CI, 0.91–0.99); I 2, 2.0%; moderate‐certainty evidence). A trend towards a lower rate of composite adverse perinatal outcome was found in women undergoing IOL using a Foley catheter compared with oral misoprostol (RR, 0.71 (95% CI, 0.48–1.05); I 2, 14.9%; low‐certainty evidence). Composite adverse maternal outcome did not differ between the groups (RR, 1.00 (95% CI, 0.97–1.03); I 2, 0%; moderate‐certainty evidence). Meta‐analyses of effect modifications did not show significant interactions between intervention and parity or gestational age for any of the primary outcomes. Conclusions: For women undergoing IOL, Foley catheter is less effective than oral misoprostol, as it was associated with fewer vaginal births. However, while we found no significant difference in maternal safety, Foley catheter induction may reduce adverse perinatal outcomes. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd. Abstract : A video abstract of this article is available online here . This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Sonda de Foley frente a misoprostol oral para la inducción del parto: metaanálisis de datos de participantes individuales Objetivo: Comparar la eficacia y la seguridad de la sonda de Foley y del misoprostol oral para la inducción del parto (IDP). Métodos: Se hizo una búsqueda en la Cochrane Review on Mechanical Methods for Induction of Labour y en Ovid MEDLINE, EMBASE vía Ovid, Ovid Emcare, CINAHL Plus, ClinicalTrials.gov y Scopus, desde su inicio hasta abril de 2019, de ensayos controlados aleatorizados (ECA) que compararan la sonda de Foley con el misoprostol oral para la IDP de gestaciones viables con feto único. Se incluyeron todos los ensayos elegibles, de los que se obtuvieron datos brutos, y se realizó un metaanálisis de los datos de las participantes individuales. Las medidas de resultado primarias fueron el parto vaginal, un conjunto de resultados perinatales adversos (como el éxitus fetal, la muerte neonatal, las convulsiones neonatales, el ingreso en la unidad de cuidados intensivos neonatales, una afectación respiratoria grave o el síndrome de aspiración de meconio) y un conjunto de resultados maternos adversos (como el ingreso en la unidad de cuidados intensivos, infección materna, hemorragia puerperal grave, la muerte de la madre o la rotura uterina). La calidad de los ECA incluidos se evaluó mediante la herramienta Cochrane de Riesgo de Sesgo 2 y la certeza de la evidencia se evaluó mediante el enfoque GRADE. Se empleó un modelo de efectos aleatorios de dos etapas para el metaanálisis según el principio de intención de tratar y se evaluaron las interacciones entre el tratamiento y las características de los valores de referencia iniciales. Resultados: De siete ensayos elegibles, cuatro proporcionaron datos de participantes individuales, para un total de 2815 participantes sometidas a IDP, de las cuales 1399 fueron asignadas a la sonda de Foley y 1416 al misoprostol oral. Los cuatro ensayos proporcionaron datos para cada uno de los resultados primarios en las 2815 mujeres. En comparación con las que recibieron misoprostol oral, las asignadas a la sonda Foley tuvieron una probabilidad ligeramente menor de tener un parto vaginal (cociente de riesgo [CR], 0, 95 (IC 95%, 0, 91–0, 99); I2, 2, 0%; evidencia de certeza moderada). Se encontró una tendencia hacia una tasa menor del conjunto de resultados perinatales adversos en las mujeres que se sometieron a una IDP mediante sonda de Foley, en comparación con el misoprostol oral (CR, 0, 71 (IC 95%, 0, 48–1, 05); I2, 14, 9%; evidencia de certeza baja). El conjunto de resultados maternos adversos no difirió entre los grupos (CR, 1, 00 (IC 95%, 0, 97–1, 03); I2, 0%; evidencia de certeza moderada). Los metaanálisis de las modificaciones de los efectos no mostraron interacciones significativas entre la intervención y la paridad o la edad gestacional para ninguno de los resultados primarios. Conclusiones: En los casos de mujeres que se sometieron a la IDP, la sonda de Foley es menos eficaz que el misoprostol oral, ya que se asoció a un menor número de partos vaginales. Sin embargo, aunque no se encontraron diferencias significativas en la seguridad materna, la inducción con sonda de Foley puede reducir los resultados perinatales adversos. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd. 摘要: 福利导管 vs 口服米索前列醇引产:个体受试者荟萃数据分析 目的: 比较福利导管与口服米索前列醇引产的临床效果与安全性(IOL)。 方法: 用考克兰法来回顾引产的机械方法以及从开始到2019年四月用Ovid MEDLINE, EMBASE via Ovid, Ovid Emcare, CINAHL Plus, ClinicalTrials.gov 和 Scopus 来索引有关福利导管和口服米索前列醇用于发育中的单胞胎妊娠进行引产的随机对照试验(RCTs)对符合条件的试验采集了其原始数据并对个体受试者的数据进行了荟萃分析。主要预后为阴道分娩，综合围产期不良预后(包括死产，新生儿死亡，新生儿癫痫发作，入院新生儿重症监护病房，严重呼吸衰竭或胎粪吸入 综合征)以及孕产妇不良预后的综合因素(包括入住重症监护病房，孕产妇感染，严重的产后大出血，孕产妇死亡或子宫破裂)。使用考克兰偏倚风险2工具评估了纳入的随机对照试验(RCT)的质量，并使用GRADE评定方法评估了证据的确定性。根据意向性治疗原则 采用两段式随机效应模型进行荟萃分析，并评估了治疗与基线特征之间的相互作用。 结果: 七项满足条件的试验中，有四项提供了总共2815名个体受试者， 接受引产的数据，其中1399名被给予給福利导管而1416名给以口服米索前列醇。所有四项试验均提供了所有2815名妇女的主要预后数据。与接受口服米索前列醇的受试者相比，福利导管使用者的阴道分娩机会略有降低(风险比(RR)为0.95(95%CI，0.91‐0.99)； I2，2.0%；中度确定性证据)与口服米索前列醇相比，使用福利导管进行引产的妇女综合围产期不良预后发生率呈降低趋势(RR，0.71(95%CI，0.48–1.05)； I2，14.9%；低确定性证据)。两组之间的产妇综合不良预后无差异(RR，1.00(95%CI，0.97‐1.03)； I2，0%；中度确定性证据)。对任何主要预后的效应修饰进行荟萃分析后均未发现干预和 胎孕次数以及胎龄之间有任何重大的相互作用。 结论: 对于接受引产的女性，福利导管的效果不如口服米索前列醇， 因为它与 较少的阴道分娩有关。然而，尽管我们发现孕产妇安全性没有显着差异，但福利导尿管可减少不良的围产期预后。版权 © 2020 ISUOG。由威利父子公司(John Wiley & Sons Ltd)出版。